Impacts of cold air on the performance of cardiopulmonary function and athletic skills in synchronized swimming - Zhang, J. (Revista Brasileira de Medicina do Esporte, 2023)
Introduction: Synchronized swimming is a sport that demands high cardiopulmonary capacity from the athletes, physical conditioning, excellent swimming, and aerobic metabolism preparation. Long-term exposure to cold air is a key factor that affects lung function, affecting the athlete`s performance in synchronized swimming. This exposure can lead to inflammation of the athletes` airways, although few studies have analyzed the changes in cardiorespiratory conditioning during competition.